Rural poverty, growth and macro-economic policies: the Asian experience - Islam, Rizwanul
By and large, developing Asian countries were more successful at alleviating rural poverty in the 1960s. While high growth is an essential precondition for poverty alleviation, it cannot be a sufficient condition perse unless the pattern and mechanism of growth are such as to ensure that the poor benefit in the process. The pattern of growth in developing Asia during the past two decades was more conducive to increasing the incomes of the poor than in the 1960s. Appropriate macroeconomic policies in the areas of trade, exchange rates, taxation, credit, subsidies, etc. are shown to have an important role to play in poverty reduction. Reproduced
Keywords: World Development Report; Rural; Price Policy overty; Asia; Agricultural Policy; Poverty - Asia